Identifikasi Drug Related Problems (DRPs) Pasien Hipertensi di RS Multazam Kota Gorontalo - Tuloli, Teti S.; Sy. Pakaya, Mahdalena; dwi pratiwi, susi (Jurusan Farmasi Universitas Negeri Gorontalo, 2021)
Hypertension is a disease that continues to increase every year, where the keys to success for its treatment are selection and use of the drugs. The treatment failure occurred if the selection and use of medication are inappropriate with the condition of patients followed by DRPs. Unresolved hypertension can cause heart attack, kidney failure and stroke. The research aimed to identify DRPs at hypertension patients with or whitout comorbidity reviewed from the drug without indication, indication without drug, high doses, low doses, and drug interaction. The research was non-experimental descriptive research which applied cross-sectional design by collecting data through a retrospective at hypertension with or without comorbidity at Multazam Hospital of Gorontalo City for January-December 2018 periods. The samples were selected by purposive sampling and obtained 79 patients who were qualified as samples. The obtained data were analyzed with univariate. The finding of research showed that the use of medication at hypertension patient with or without comorbidity at Multazam Hospital of Gorontalo City for January-Desember 2018 periods based on five categories were drug without indication was 3.08%, indication without drug was 33,84%, high doses was 27,70%, low doses was 4,62% and drug interaction was 30,76%. The identification of DRPs of use of hypertension medication with or without comorbidity at Multazam Hospital of Gorontalo City for January-December 2018 periods was categorized good.